DEVELOPING THE INSTITUTIONAL FRAMEWORK OF SOUTH AFRICA AND THE NEIGHBORING STATES FOR THE PURPOSE OF ATTRACTING FOREIGN DIRECT INVESTMENTS - D. Fogel (Вестник университета, 2017)
South Africa needs to reconsider its investment policy in order to change the current state of foreign direct investments (FDI) inflows. It is also necessary to coordinate national and international measures to assure balanced economic growth. Of particular significance also are initiatives to set up information networks that can provide foreign entrepreneurs with contemporary information on the current and promising investment projects in Africa. State bodies of South Africa need to promote the FDI inflows and offer stimuli for maintaining the high rate of sustainable economic development.